DETEKSI DAN FAKTOR RESIKO KEJADIAN AVIAN INFLUENZA PADA PETERNAKAN AYAM KOMERSIAL DI KABUPATEN MAROS - , FAIZAL ZAKARIYA ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Chicken commercial farm(s) could be a part of the potential source of Avian influenza (AI) infection. Chicken commercial farm(s) in Maros district have instituted biosecurity system to prevent and control of AI. Based on the diagnosis records of Disease Investigation Centre (DIC) Maros, incidence of AI in Maros during the last five years have decreased. Even in 2010, there was no AI case found. Maros is located geographically adjacent to AI infected area and, therefore, is prone to the infection. The objectives of this study were to detect AI in chicken commercial farms in Maros and to measure the association between AI and risk factors of biosecurity and farmerâs knowledge. Simple random sampling method was used to choose 142 out of chicken commercial farms in Maros district. Swab specimens were taken from purposively sampled chicken from the farm. Pooling of 5 chickens oropharingeal/trachealâs swabs at the same age and cages of each farms were taken to detect the presence of AI virus by means of virus isolation and HA/HI test in DIC Maros. A farm defined as infected if it showed positive result from virus isolation and HA/ HI test. The results showed that some of chicken commercial farms in Maros infected by AI virus. Bivariate analysis showed that risk factors of biosecurity and farmer knowledge which associated with AI evidence were the experience of farmer, sub district Camba and Malawa, mixed raising system, the existence of farmer or farmer worker who also work at another farm/wholesaler/trading poultry market, people traffic from infected to healthy cages, mutual use other farmâs tool and feed, absence of water tank disinfection, absence of water chlorination, no closed litter storage, rest period less than 15 days, no inspection program from animal health officer, and vaccination only in case of the death of chicken. Multivariate unweigthed logistic regression analysis showed that f mutual use other farmâs tool and feed (OR=385,99) and people traffic from infected to healthy cages (OR=771,98) were significantly associated with AI infection. The findings suggest the necessities of chicken commercial farmers to do risk assessment, risk monitoring, risk communication and evaluation of biosecurity system. Improvement of Maros district animal health services on poultry and enforcement of biosecurity are needed.